Risk factors for stunting in children who are HIV‐exposed and uninfected after Option B+ implementation in Malawi - Gabriela Toledo; Megan Landes; Monique vanLettow; Beth A. Tippett Barr; Heather Bailey; Siobhan Crichton; Wezi Msungama; Claire Thorne (Wiley, 2023)
Abstract Evidence suggests children HIV‐exposed and uninfected (CHEU) experience poor growth. We analysed child anthropometrics and explored factors associated with stunting among Malawian CHEU. Mothers with HIV and their infants HIV‐exposed were enroled in a nationally representative prospective cohort within the National Evaluation of Malawi's Prevention of Mother‐to‐Child HIV Transmission Programme after Option B+ implementation (2014-2018). Anthropometry was measured at enrolment (age 1-6 months), visit 1 (approximately 12 months), and visit 2 (approximately 24 months). Weight‐for‐age (WAZ) and length‐for‐age (LAZ) z‐scores were calculated using World Health Organization Growth Standards; underweight and stunting were defined as WAZ and LAZ more than 2 standard deviations below the reference median. Multivariable logistic regression restricted to CHEU aged 24 months (±3 months) was used to identify factors associated with stunting. Among 1211 CHEU, 562/1211 attended visit 2, of which 529 were aged 24 months (±3 months) and were included. At age 24 months, 40.4% of CHEU were stunted and/or underweight, respectively. In multi‐variable analysis, adjusting for child age and sex, the odds of stunting were higher among CHEU with infectious disease diagnosis compared to those with no diagnosis (adjusted odds ratio = 3.35 [95% confidence interval: 1.82-6.17]), which was modified by co‐trimoxazole prophylaxis (p = 0.028). Infant low birthweight was associated with an increased odds of stunting; optimal feeding and maternal employment were correlated with reduced odds. This is one of the first studies examining CHEU growth since Option B+. Interventions to improve linear growth among CHEU should address their multi‐faceted health risks, alongside maternal ART prescription, and follow‐up of mother‐child pairs.